Scale effect for hydraulic model of a mixed flow nuclear main pump - Tao Zhou; Yong Zhu; Shengnan Tang (Nuclear Engineering and Technology)
Optimizing the hydraulic components of nuclear main pump (NMP) and conducting performance verification is crucial. Due to the large size of the real NMP, the strict requirements of the operation and the high test-cost, there are many difficulties in the real test. The mixed flow NMP is taken as the research object, and the CAP1400 NMP is selected as the prototype pump (PP). The model pumps (MPs) with varying scales are established based on the similarity conversion algorithm (SCA). Then, the influence of different scales on the hydraulic performance and internal flow field is investigated and compared. It is demonstrated that the predicted value of head is 4 % higher than the design value at the design operating point, and the maximum efficiency point is close to the design operating point. In the range of full flow conditions, the head, hydraulic efficiency, impeller efficiency, guide vane energy loss, internal flow field, and vorticity distribution of PP and MPs are basically consistent with the trend of flow rate variations. The PP and MPs conform to the SCA. The hydraulic design and performance optimization of NMP are achieved by using the model proportional scaling approach.